EFEKTIVITAS METODE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNRI PADA MATA KULIAH KAIWA 5 - Azhar, Khansa Nabila; Hadriana, Hadriana; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research discusses about the application of Make a Match method in the 5th semester of Japan study program students in Kaiwa subject. The aim of this study was to describe the effectiveness of Make a Match method in improving students Japan study program’s learning outcomes. For this study, the writer used weak experiment research design that was marked by not given a comparison class. The data collection technique that used by giving a test. The result on the Pre-test and Post-test has improvement. The average of students’ Pre-test was 70, while the average of students’ Post-test was 80. The result of the test was processed using T- statistical tests to find out how significant the level of students’ learning outcomes when using Make a Match method. Based on the table output ‘One Sample Test’ above, known sig value is 0.696 < 0.05, then according with the basis of decision making, it could be concluded that Ho was accepted and H1 was rejected. It means that there is significant influences on the use of Make a Match method. This method is effective in improving students learning outcomes in Japan Study Program; Faculty of Education at the University of Riau in Kaiwa Subject.Keywords: effectiveness, Make a Match method, Kaiwa, Japanese language